Spontaneous low-protein intake in older CKD patients: one diet may not fit all - Vettoretti, Simone; Molinari, Paolo; Armelloni, Silvia; Castellano, Giuseppe; Caldiroli, Lara (Frontiers in Nutrition, 2024)
Background: Protein restriction has been extended to stage 3 chronic kidney disease (CKD) regardless of age in the latest K-DOQI guidelines for the dietary management of patients with chronic kidney disease (CKD). However, in elderly CKD patients there is a tendency to a spontaneous reduction in protein and energy intake that may impair the overall nutritional status. The aim of our study is to assess whether there are differences in malnutrition, exercise capacity and inflammatory status in elderly CKD patients with spontaneously reduced low protein intake (sLPI) compared with patients with normal protein intake (NPI).Methods: we performed a cross-sectional analysis of 123 incident patients. Malnutrition was assessed using Malnutrition Inflammation Score (MIS) and serum markers; As for physical performance, we used Short Physical Performance Battery (SPPB) and handgrip strength.Results: we found that in older patients with advanced CKD, as many as 68% had low spontaneous protein intake, and they were more malnourished evaluated with MIS (25% vs 10%, p=0.033), proteinenergy wasting (and PEW) (43% vs 14%, p=0.002) and nPCR (0.